Screening for autism spectrum disorder in a naturalistic home setting using the systematic observation of red flags (SORF) at 18–24 months. Issue 1 (23rd October 2019) - Dow, Deanna; Day, Taylor N.; Kutta, Timothy J.; Nottke, Charly; Wetherby, Amy M.
Abstract : The purpose of this study was to examine the utility of the Systematic Observation of Red Flags (SORF; Dow et al., 2016) as a level 2 screener for autism spectrum disorder (ASD) in toddlers during a naturalistic video‐recorded home observation. Psychometric properties of the SORF were examined in a sample of 228 toddlers—84 with ASD, 82 with developmental delay (DD), and 62 with typical development (TD). Trained undergraduate research assistants blind to diagnosis rated 22 red flags (RF) of ASD associated with DSM‐5 diagnostic criteria using a 4‐point scale. The following scores were computed: a total score summing all items, domain scores summing social communication and restricted, repetitive behavior items, and number of RF counting items with scores of 2 or 3 indicating clear symptom presence. The performance of the total, domain, and RF scores and individual items were examined. A composite score was formed with six items with the best psychometric performance: poor eye gaze directed to faces, limited showing and pointing, limited coordination of nonverbal communication, less interest in people than objects, repetitive use of objects, and excessive interest in particular objects, actions, or activities. The 6‐item composite provides a brief measure with optimal performance, while the RF may be instrumental for clinicians who are interested in characterizing the range of observed symptoms. The SORF shows promise as a practical alternative to currently available screening methods for implementation by nonexperts with the potential to increase feasibility and reduce common obstacles to access to care. Autism Res 2020, 13: 122–133 . © The Authors. Autism Research published by International Society for Autism Research published by Wiley Periodicals, Inc. Lay Summary: Research suggests that current autism spectrum disorder (ASD) screening tools are not accurate enough to use in routine screening. The Systematic Observation of Red Flags was developed as a practical option for children at high risk for ASD. It can be used with video‐recorded samples of parent–child interactions in the home and by raters who are not experts in ASD. It shows promise in predicting ASD risk in toddlers to determine if a full diagnostic evaluation is necessary.